Wealth Effects from Banks Mergers and Acquisitions in Eastern Europe - Kyriazopoulos, Georgios (International Journal of Economics and Financial Issues, 2016)
The main objective of the current study is the examination of the wealth effects emanating from the announcement of mergers and acquisitions (M&As) in Eastern Europe that took place between 1995 and 2015. In specific, the main objective of the paper is the examination of the stock price reaction of both bidders and targets to the announcement of M&As. The method of payment is another aspect that is considered when assessing the wealth effects of M&As. To gauge market reaction, we use both the standard event study methodology and regression analysis. The results show that targets gain significant abnormal returns around event periods, while acquirers seem to earn trivial excess returns. Moreover, cash disbursements in bank M&As boost price appreciations around event dates. The results from regression analysis reveal that the determinants of abnormal returns are the market competitiveness, method of payment, and relative size. Keywords: Mergers, acquisitions, wealth effects, abnormal returns, Eastern Europe. JEL classifications: G11; G14, G21; G34